Pengaruh Penambahan Silika (SiO2) Sekam Padi Terhadap Karakteristik Mikrostruktur dan Struktur Aspal dengan Perbandingan Massa 1:0 ; 1:1,5 ; 1:1,6 dan 1:1,7 - Letia Oktri Diana; Simon Sembiring; Rudi T.M Situmeang (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2019)
Synthesis and characterization of silica rice husk blend asphalt was carried out with a mass ratio of 1;0; 1:1,5; 1:1,6 and 1:1,7 respectively. Rice husk was prepared by sol-gel method as a raw material of silica. Asphalt and silica is mixed by using the solid-sate method, which is heated with a temperature of 110 oC for 4 hours. This study was revealed to investigate the effect of the addition of silica from rice husk on microstructure and asphalt structure. SEM results show the morphology of the asphalt surface without addition of silica which transforms elongated folds and after addition of silica shows uncertain granules more likely seems clusters with grain size (1:1,5 = 4,298 ?m, 1:1,6 = 3,103 ?m and 1:1,7 = 5,328 ?m) respectively. The XRD results show asphaltene amorphous phase in the asphalt sample with two peaks at 2?= 18,90? and 2?= 42?. Furthermore, the addition of silica with asphalt able to modify two asphaltene peaks into carbon and silica amorphous peaks.